PANDANGAN UNDANG-UNDANG NO. 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN TERHADAP PERJANJIAN BAKU - Abdul Latif (Jurnal Ilmiah Cano Ekonomos, 2017)
Standard contract is an agreement whose contents are made by one party only, while others do not have the opportunity to negotiate or ask for a change to the contents. The purpose of this study is to see the validity of the standard contract when viewed from the perspective of Law No. 8 of 1999 on Consumer Protection . This study uses normative juridical method , using data sources , such as primary legal materials , secondary legal materials , and tertiary legal materials . Then the data obtained was done using descriptive method of analysis . Results of this research is that in the view of the Law No. 8 of 1999 on Consumer Protection , the raw agreement is not prohibited along the raw contents of the agreement does not contain terms that contain conditions restricting or removing entirely the responsibility borne by the employer